Efficacy of Some Formulations of the Insecticide Chlorpyrifos against Microcerotermies diversus Silv. On Citrus Tree Orchards - Taha, H.A.; Hussain, M.S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The eflicacy of six formula from chloropyrifos against tem1ite Microterotermes - diversus on citrus tree orchards has been tested years . Data!rom field trials confirmed that Dursbau 4TC, chlorpyrifos - 500 EC and Talaban 40,8 TC at rate 100 mL L protected citrus trees for two years. While ch1orfate. 40.8 TC, Dormate 40,8TC, Yamasban 40,8 TC protected them for 16,16 and 12 months respectively at the same concentration. But the rate of 5m1/ L of Dursban, chropyfros 500 EC , Chlorfat, Tafabun yamashan and Dormate protected the trees tor 24,16,4,4,2 and 4 months , respectively .